Enhancing Students’ Technopreneurship Projects with Mobile Collaboration and Communication Application - Wahyudi, Stephanus Eko; Tileng, Kartika Gianina; Kurniawan, Ian Budi (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Technopreneurship subjects are a series of 3- semester subjects at Universitas Ciputra. Students usually take these subjects during their final years, which invoke problems, such as less frequent campus visit, motivation lost, miss milestones deadline, and many more. Information and Communication Technologies application can be used to promote the bond between lecturers/supervisors with students and among the students. Mobile collaboration and communication application allow the students to get notifications, relevant resources, communicate and collaborate. The mobile apps discussed in this paper is part of an integrated system which also includes a website. It was developed using SDLC methodology. Firebase cloud service developed by Google is used as the backend, including Firebase Real-time Database, Firebase Storage, and Firebase Cloud Functions. The result is that the application is easy to use and useful as a mean of support that helps the students to complete the subject series.